Newborn gender as a predictor of neonatal outcome in mixed gender twins born with very low birth weight - Bernard Barzilay; Nina Shirman; Haim Bibi; Ibrahim Abu-Kishk (BMC, 2019)
Abstract Background Most studies have revealed that the incidence of morbidity and mortality of preterm male infants is greater than that of preterm female infants. Recently, conflicting outcomes have been reported regarding mixed-gender twins. The aim of this study was to estimate the association between gender and outcome in newborn twins of different gender. Methods We conducted a retrospective review of mixed-gender twins weighing < 1500 g that were born at Shamir Medical Center (Assaf Harofeh) between the years 1995 and 2016 (158 newborns). The incidence of morbidity and mortality until discharge from the hospital were evaluated while looking at gender differences. Results No significant differences were found in neonatal mortality or morbidity between females and males from different-gender twins. Even after considering confounding variables (gestational age, birth weight & birth order) in linear and logistic regression models, no significant differences were found between the genders. Conclusions Our study suggests that there are no significant differences in neonatal mortality or morbidity among different-gender twins. Our results support the need for further studies.